BEING SAFE ONLINE : A First Look - Peters, Katie; Craig, Diane; Certified Literacy Specialist (Minneapolis : Lerner Publications, 2024)
"It's important that kids know how to be safe online. With easy-to-read text and engaging photographs, this book makes digital citizenship simple for young children to learn"-- Provided by publisher
Being safe online -- You connect! -- Social and emotional snapshot.
Includes bibliographical references and index.
Keywords: Internet and children -- Juvenile literature; Internet -- Safety measures -- Juvenile literature; Juvenile works